Molecular characterization and antibiotic resistance of Streptococcus dysgalactiae subspecies equisimilis isolated from patients with streptococcal toxic shock syndrome. Issue 2 (February 2018) - ,; Morimoto, Y.; Sakamoto, Y.; Sato, S.; Musashi, M.; Shirasawa, A.; Konno, T.; Kobayashi, T.; Watanabe, Y.; Seto, J.; Kobayashi, Y.; Sakai, K.; et al.
Abstract: Streptococcal toxic shock syndrome (STSS) is a severe invasive infection characterized by the sudden onset of shock, multiorgan failure, and high mortality. Although STSS is mainly caused by Streptococcus pyogenes, group G streptococcus identified as S. dysgalactiae subsp. equisimilis (SDSE) causing STSS has also been reported; however, no study has analyzed >100 isolates of SDSE causing STSS. Therefore, we characterized the emm genotype of 173 SDSE isolates obtained from STSS patients in Japan during 2014–2016 and performed antimicrobial susceptibility testing using the broth microdilution method and emm gene typing. The predominant emm genotype was found to be stG6792, followed by stG485, stG245, stG10, stG6, and stG2078. These six genotypes constituted more than 75% of the STSS isolates. The proportion of each emm genotype in STSS isolates correlated with that in invasive isolates previously reported. We found that 16.2% of the isolates showed clindamycin resistance. The proportion of clindamycin-resistant SDSE isolates was significantly higher than that of S. pyogenes isolates. Thus, while treating STSS caused by SDSE, it is necessary to consider the possibility of clindamycin resistance and to ensure judicious use of the drug.